If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -12 = 9x + 18 Reorder the terms: -12 + 15x = 9x + 18 Reorder the terms: -12 + 15x = 18 + 9x Solving -12 + 15x = 18 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -12 + 15x + -9x = 18 + 9x + -9x Combine like terms: 15x + -9x = 6x -12 + 6x = 18 + 9x + -9x Combine like terms: 9x + -9x = 0 -12 + 6x = 18 + 0 -12 + 6x = 18 Add '12' to each side of the equation. -12 + 12 + 6x = 18 + 12 Combine like terms: -12 + 12 = 0 0 + 6x = 18 + 12 6x = 18 + 12 Combine like terms: 18 + 12 = 30 6x = 30 Divide each side by '6'. x = 5 Simplifying x = 5
| 3(2t+6)=0 | | 12y+y^2=6y | | 535(64+646)53= | | 7=-2(-3-y) | | 5+2y=15 | | -3(n+2)=12 | | 2(4-3m)=13 | | 3(5+2x)=8(5+x) | | 64-4x=32x+24 | | 5(x-6)=-15 | | (6t-1)+(4t+2)+(7t+3)+3t=124 | | 4y^3-2=1y-8y^2 | | 6x+10=-120-7x | | 5(2+3+x)=110 | | 2y+10=2y+5 | | 2j(7j^2+jk^2+5k)-9k(-2j^2k^2+2k^2+3j)=0 | | t-4=21 | | t-4=24 | | 2.5x+1.5x=6 | | 15x^3-12x^2+3x= | | -20=-4+z | | -20=-4+7 | | 3x-50=1 | | 6+1x-10x^2=0 | | 7x-50=1 | | -10=-n+2-2n | | -14x^3-7x^2= | | 3x*27723355675= | | (x-6)7=49 | | 3x*2= | | 12=2x-7x-8 | | 9x^2+6x-1=0 |